Relationship Between Training Load, Fitness, and Injury Over an Australian Rules Football Preseason. Issue 10 (October 2017) - Harrison, Peter W.; Johnston, Rich D.
Abstract : Abstract: Harrison, PW and Johnston, RD. Relationship between training load, fitness, and injury over an Australian rules football preseason. J Strength Cond Res 31(10): 2686–2693, 2017—Recent research identifies that certain training load (TL) patterns increase the injury risk to athletes. However, physical fitness must also be considered to establish optimal TL patterns. The aim of this study was to identify TL patterns optimal for injury and aerobic fitness by exploring the TL-injury and TL-fitness relationship concurrently over an Australian rules football (ARF) preseason. Individual TL, aerobic fitness, and injury data were collected over a 14-week preseason in 60 subelite ARF players (age = 21.3 ± 2.9 years). Individual TL, assessed through session rating of perceived exertion (sRPE), was compared with noncontact, lower limb soft tissue injury to examine the TL-injury relationship. A 2-km time trial was used as the measure of aerobic fitness to examine the optimal TL for aerobic fitness improvement. Aerobic fitness improved by 4.10 ± 2.20% (range = −7.35–19.05%) over the preseason. Training load between 1, 600 and 2, 000 AU per week was associated with the greatest aerobic fitness improvement (effect size [ES] = 0.47–1.01). Players with preseason TL <1, 250 AU per week had the highest injury rate (ES = 0.52–0.62). Large 2-week TL (>4, 000 AU, odds ratio [OR] = 2.80) and spikes in weekly TL (15–49%, OR = 3.76) significantly increased injury risk the following week. Performing small amounts of training seems to be the most detrimental to changes in aerobic fitness and injury rate. High TL is not responsible for injuries and is required to maximize improvements in aerobic fitness. However, TL exceeding 2, 000 AU over several weeks may attenuate aerobic fitness improvements and increase injury risk. In addition, large increments in weekly TL increase injury risk.